2018
DOI: 10.5191/jiaee.2018.25307
|View full text |Cite
|
Sign up to set email alerts
|

A Survey to Determine International Program Growth Areas and Needs to Guide a College of Agriculture International Programs Office

Abstract: International programs (IP) continue to grow in importance. There is an increased demand from employers and communities for globally competent individuals, yet only 2.3% of Dale Bumpers College of Agricultural, Food and Life Sciences (Bumpers College) students studied abroad in an agriculture-related program during the 2014 and 2015 academic year. This study used descriptive survey methods with University of Arkansas undergraduate students enrolled in Fall 2017 Bumpers College courses (n = 1,758) to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 9 publications
(23 reference statements)
6
14
0
Order By: Relevance
“…Students also stated that "I have a fear of traveling outside of the U.S. was the least perceived barrier to participating in an IP (M = 1.69, SD = 1.11) (see Table 1). These findings were consistent with previous research by Edgar et al (2018). Respondents identified the top two perceived benefits to participating in an IP as "socially/ culturally learn more about a host country" (M = 4.61, SD = 0.67) and "life-changing opportunity" (M = 4.60, SD = 0.66) (see Table 2).…”
Section: Findings and Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Students also stated that "I have a fear of traveling outside of the U.S. was the least perceived barrier to participating in an IP (M = 1.69, SD = 1.11) (see Table 1). These findings were consistent with previous research by Edgar et al (2018). Respondents identified the top two perceived benefits to participating in an IP as "socially/ culturally learn more about a host country" (M = 4.61, SD = 0.67) and "life-changing opportunity" (M = 4.60, SD = 0.66) (see Table 2).…”
Section: Findings and Resultssupporting
confidence: 90%
“…Short-term programs are an important alternative for students that would not participate in semester-long or yearlong IPs (Lewis & Nisenbaum, 2005). Edgar et al (2018) reported that 71% of students surveyed were interested in short-term, faculty-led programs. However, many semester-length and longer programs are meant to be immersive and designed to eliminate "cultural bubbles" by incorporating volunteerism, service-learning, internships, and homestay experiences, which have well documented benefits (Anderson, 2019).…”
Section: Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations